Using matrix-induced ion suppression combined with LC-MS/MS for quantification of trimethylamine-N-oxide, choline, carnitine and acetylcarnitine in dried blood spot samples - Lu, Wan-Hui; Chiu, Huai-Hsuan; Kuo, Han-Chun; Chen, Guan-Yuan; Chepyala, Divyabharathi; Kuo, Ching-Hua (Analytica chimica acta, 2021)
Recently, there has been significant interest in the influences of the human gut microbiota on many diseases, such as cardiovascular disease (CVD) and metabolic disorders. Trimethylamine N-oxide (TMAO) is one of the most frequently discussed gut-derived metabolites. Dried blood spot (DBS) sampling has been regarded as an attractive alternative sampling strategy for clinical studies and offers many advantages. For DBS sample processing, whole-spot analysis could minimize hematocrit-related bias, but it requires blood volume calibration. This study developed a method combining matrix-induced ion suppression (MIIS) with liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) to estimate blood volume and quantify TMAO and its precursors and derivatives, including choline, carnitine and acetylcarnitine, in DBSs. The MIIS method used an ion suppression indicator (ISI) to measure the extent of ion suppression caused by the blood matrix, which was related to the blood volume. The results showed that the volume estimation accuracy of the MIIS method was within 91.7–109.7%. The combined MIIS and LC-MS/MS method for quantifying TMAO, choline, carnitine and acetylcarnitine was validated in terms of linearity, precision and accuracy. The quantification accuracy was within 91.2–113.2% (with LLOQ <119%), and the imprecision was below 8.0% for all analytes. A stability study showed that the analytes in DBSs were stable at all evaluated temperatures for at least 30 days. The validated method was applied to quantify DBS samples (n = 56). Successful application of the new method demonstrated the potential of this method for real-world DBS samples and to facilitate our understanding of the gut microbiota in human health. [Display omitted] •We developed a method to quantify TMAO and its precursors and derivatives in DBSs.•The MIIS method can be used to correct blood volume for polar metabolites in DBSs.•Validation results indicated that the quantitation was precise and accurate.•The developed method was applied to analyze 56 real paired plasma/DBS samples.